VIDEO GAMES AND WORKING MEMORY PERFORMANCE - Sharifah Sophia Shahirah, Wan Akil (Universiti Malaysia Sarawak, (UNIMAS), 2021)
The aim of study was to investigate the relationship between video games and working memory performance among university students by focusing on two categories of video games which is serious and commercial games by conducting a dual task of verbal recall. The first objective of the study was to investigate the differences in the means of correct verbal recall between serious, commercial and no video games group and the second objective was to determine the differences in the means of correct verbal recall between before and after playing video games. The study conducted an experiment with 30 participants that are equally divided into three group which are serious game, commercial game, and no video game group. The serious game and commercial game groups will play Minecraft and Pubg as the intervention for 30 minutes respectively while the no video game group will have no intervention. A pre-test and post-test of results of verbal recall task was recorded. The findings to the first objective utilized one-way ANOVA and found that there were no significant differences of correct verbal recall between serious, commercial and no video game group while the findings to the second objective utilized paired sample t-test and resulted in no significant differences between before and after playing video games. It was discovered that mental states such as attention, motivation, mind-wandering and emotional were factors in the resulting outcomes. Overall, the study had found that there were no differences between the relationship of video games and working memory performance